Retinal Findings in Hospitalized COVID-19 Patients, Is Routine Ophthalmological Examination Required after Discharge? Prospective Case-Control Study - Akalin, Irfan; Kalkisim, Ahmet; Gunay, Betul Onal; Esenulku, Cenap Mahmut (Klinische Monatsblätter für Augenheilkunde, 2023)
Objectives To investigate retinal findings by comparing patients hospitalized for COVID-19 with the control group.Methods In this prospective study, 188 eyes of 94 recovered COVID-19 patients and 108 eyes of 54 healthy participants as a control group were evaluated. Patients were divided into three groups, those with mild, moderate, and severe COVID-19. Refractometry, tonometry, optical biometry, optical coherence tomography (OCT) measurements, and complete ophthalmological examinations were performed on healthy volunteers and COVID-19 patients on average 2 weeks after discharge. Pulse O2 and vital parameters were also assessed. Primary outcomes were evaluated, such as retinal findings, and secondary outcomes as retinal thickness, choroidal thickness (CT), retinal nerve fiber layer thickness, and ganglion cell layer thickness.Results There was no difference between the groups in terms of demographic data, ocular biometry, and intraocular pressure (p > 0.05). Pulse O2 was lower in the study group (p < 0.001). Retinal findings were detected in 68 (36.1%) of 188 eyes in the study group and 28 (25.9%) of 108 eyes in the control group (p = 0.07). The two most common retinal findings were hypertensive retinopathy and retinal pigment epithelium alterations and/or drusen in both groups. In OCT measurements, significant thinning was observed in nasal macular thickness and superior 2 mm CT in the study group compared to the control group (p < 0.05). In patients divided into subgroups according to disease severity, no significant difference was found between the groups in any OCT parameter (p > 0.05).Conclusion It has been observed that COVID-19 infection does not cause a specific and sensitive finding in the ocular tissues, especially the retina, and does not produce a reproducible measurement result. Recommending routine eye exam after COVID-19 does not seem cost-effective.
Keywords: choroid; cotton wool spots; COVID-19; OCT; retina